Routes to the information revolution - Arbel, Alexander (Cambridge Scholars Publishing, 2019)
This book is a precise and comprehensive history of the digital computer. It is the first collection of available information about the digital computer, beginning with the philosophical and logical advancements in the early 20th century that led to it. The book explores the histories and stories of the computer, tracing its roots and routes. It examines and analyzes commonly accepted views on the digital computer and its development, and offers clearer and more accurate alternatives to them. Its approach, though dealing with the introduction and development of the digital computer, is applica.